Struktur Modal, Profitabilitas, Dan Likuiditas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Moderasi - Muhamad Riki; Naelati Tubastuvi; Akhmad Darmawan; Ika Yustina Rahmawati (Jurnal Akademi Akuntansi, 2022)
The current developments of industry are very competitive with each other, including Indonesia’s industry. The rise and fall of a company’s value is commonly seen in companies. This study aims to obtain empirical evidences and examine the effect of capital structure, profitability, and liquidity on company’s value moderated by dividend policy in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. This study uses a quantitative approach. A total of 18 companies were selected using the purposive sampling method, using the 2016-2020 period, which resulted in 90 sample data. The analytical method used in this research is multiple regression analysis and absolute difference for the moderating variable. The results showed that capital structure and profitability had positive and significant effects on company’s value, while liquidity had negative and significant effects on company’s value. And dividend policy can moderate the effect of capital structure on company’s value, but dividend policy is not able to moderate the effect of profitability and liquidity on company’s value.